Experimental Study and DEM Simulation of Size Effects on the Dry Density of Rockfill Material - Zhao, Xiaolong; Zhu, Jungao; Wu, Yunlong; Jia, Yun; Bur, Nicolas; Colliat, Jean-Baptiste; Bian, Hanbing (Frontiers in Physics, 2022)
The initial dry density has a significant effect on the mechanical behavior of rockfill material (RFM). The size effects on the minimum/maximum dry density (referred to as dry density, ρ_d) of RFM still need further study. To investigate the relationship between ρ_d and d_M, a series of dry density tests and DEM simulations are performed on the samples with different maximum particle sizes d_M. Both the physical and numerical results exhibit that ρ_d increases fast when d_M ranges from 10 to 40 mm. When d_M exceeds 40 mm, ρ_d increases slowly and tends to be a constant. Results indicate that ρ_d is affected by the gradation. To consider the gradation effect, a normalized parameter λ is introduced, and the relation between ρ_d and d_M can be characterized by an empirical equation.